Empowering Schools: Transitioning from Teacher Leadership to Innovative Principals with Agent Teachers (Current Research in Education: Conference Series Journal, 2024)
This study explores the transition of teacher leadership into innovative school principals through the Agent Teacher Program as mandated by the Ministerial Regulation No. 40 of 2021. The research aims to examine how teacher leadership can be developed and transformed into innovative educational leadership within schools and communities. Employing a qualitative approach using the Systematic Literature Review (SLR) method, the study synthesizes findings from various academic sources related to teacher leadership, agent teacher development, and innovative principalship. The results indicate that the Agent Teacher Program effectively nurtures leadership skills, independence, and innovation among teachers, enabling them to become future principals and educational change agents. This transformation contributes to improving school quality and realizing the goals of Merdeka Belajar by empowering teachers as key drivers of educational reform in Indonesia.